The dilemma of corporal punishment for teachers in two South African primary schools - Martin, Melanie (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
Corporal punishment continues to be used, albeit as a contested and abolished practice in South African schools. Using the theoretical framework of dilemmatic spaces, this article explores the various factors that created dilemmas and contestations for teachers about the practice of corporal punishment. Data were generated through qualitative, narrative semi-structured interviews. Seven teachers, teaching at two primary schools in KwaZulu-Natal, South Africa were purposively selected. The study employed the interpretivist paradigm to foreground participants’ subjective voices. The findings indicate the dilemma of corporal punishment is ever present and influenced by various contextual, ideological, religious, cultural and personal factors, that make it difficult for teachers to determine the correct response. The dilemma of corporal punishment is complex and multi-layered and teachers’ decisions ultimately rest on pragmatism rather than moral reasoning about its use. Thus, the findings suggest that corporal punishment may persist unless deeper understanding of the complexity that surrounds teachers’ professional lives are explored. The study calls for developing contextual understandings of how corporal punishment creates dilemmas for teachers’ professional and personal identities and practices. Such understandings are essential for creating effective and humane interventions at individual, institutional and systemic levels that address the complex factors influencing teachers’ practices.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 4, Volume 9, 2025
Keywords: Context; Corporal punishment; Culture; Dilemmas; Ideology; Religion; Corporal punishment; Ethical problems; Ideology; Corporal punishment of children -- South Africa -- KwaZulu-Natal; Education, Elementary -- South Africa -- KwaZulu-Natal; School discipline